Materia Constitucional N° 2009-01291-0-1903-JR-CI-2. Demandante: Ian Xavier Rengifo Vásquez. Demandado: Corte Superior de Justicia de Loreto. Materia: Acción de Amparo. Órgano jurisdiccional: Corte Superior de Justicia de Loreto - Segundo Juzgado Civil de Maynas / Materia Civil N° 2001-01012-0-1903-JR-CI-1. Demandante: Socorro Castañeda Alzamora. Demandado: Margot Freitas Pinedo, Mauro Freitas Urrelo. Materia: Desalojo. Órgano Jurisdiccional: Corte Superior de Justicia de Loreto - Primer Juzgado Civil de Maynas - Liao Torres, Cheng Poli (2022)
In the Second Specialized Civil Court of Maynas, the plaintiff Ian Xavier Rengifo Vásquez files a constitutional action for amparo against the Superior Court of Justice of Loreto, requesting that the uncaused dismissal of which he would have been subject be annulled, thus violating his fundamental right to work, and that therefore, in order to restore his violated right, he is reinstated in the position of Judicial Assistant, with an indefinite contract because the contract subject to modality has been distorted. The Judge of first instance declares the claim well founded, considering that the plaintiff's dismissal occurred without expressing a reason that justifies it, given that the plaintiff carried out tasks of a permanent nature that are inherent to the main activity of his employer and that, therefore, they coexist with it permanently and continuously; arguing with this that their constitutional right to work, due process and defense, enshrined in articles 22, 139, subsections 3 and 14 of the Political Constitution of the State, have been violated. The defendant filed an appeal. The Collegiate of the Mixed Civil Chamber of Loreto, revokes the Judgment contained in resolution No. 05 dated April 27, 2010, which declares the lawsuit filed by Ian Xavier Rengifo Vásquez founded, reforming it, declaring the lawsuit founded in part, ordering to the summoned entity to reinstate the plaintiff in the position that he had been holding or another similar one, as long as the vacant position he occupies is awarded through a selection contest, or there is any other just cause for dismissal, resulting in unfounded in the extreme of the demand tending to that the reincorporation to the job be for an indefinite term, as it has not been proven that said position was obtained through a selection contest.